Insights into the Protein–Lipid Interaction of Perivitellin-2, an Unusual Snail Pore-Forming Toxin - Romina F. Vázquez; M. Antonieta Daza Millone; Matías L. Giglio; Tabata R. Brola; Sabina M. Maté; Horacio Heras (Toxins)
The perivitellin-2 (PV2) from snails is an unusual neuro and enterotoxin comprising a pore-forming domain of the Membrane Attack Complex and Perforin Family (MACPF) linked to a lectin. While both domains have membrane binding capabilities, PV2’s mechanism of action remains unclear. We studied the apple snail Pomacea maculata PV2’s (PmPV2’s) interaction with lipid membranes using various biophysical and cell biology approaches. In vitro studies showed that PmPV2 toxicity decreased when cholesterol (Chol) was diminished from enterocyte cell membranes. Chol enhanced PmPV2 association with phosphatidylcholine membranes but did not induce pore formation. In contrast, using rat brain lipid models, rich in glycolipids, PmPV2 exhibited high affinity and induced vesicle permeabilization. Negative stain electron microscopy and atomic force microscopy confirmed the formation of pore-like structures in brain lipid vesicles. Our findings suggest that Chol is a necessary lipid component and point to PmPV2–glycolipid interactions as potential activators critical to triggering PmPV2’s pore-forming activity, providing insights into this novel toxin’s mechanism.